Case Report: Para-infectious cranial nerve palsy after bacterial meningitis - Zanotelli, Giovanni; Bresciani, Lorenzo; Anglani, Mariagiulia; Miscioscia, Alessandro; Rinaldi, Francesca; Puthenparampil, Marco (Frontiers in Immunology, 2022)
A 27-year-old woman was admitted to our hospital for fever, associated with headache, nausea, vomiting, mild left facial nerve palsy and diplopia. Neurological examination revealed a mild meningism, associated with bilateral VI cranial nerve palsy and mild left facial palsy. In the suspect of a CNS infection, a diagnostic lumbar puncture was performed, which disclosed 11,677 cells/μL, 70% of which were polymorphonuclear leukocytes. Moreover, multiplex PCR-immunoassay was positive for Neisseria Meningitis, supporting the diagnosis of bacterial meningitides. Finally, IgG Oligoclonal Bands (IgGOB) were absent in serum and cerebrospinal fluid (CSF). Therefore, an antibiotic therapy with Ceftriaxone was started, and in the next following days patient’s signs and symptoms improved, with a complete remission of diplopia and meningeal signs within a week. On contrary, left facial nerve palsy progressively worsened into a severe bilateral deficit. A second lumbar puncture was therefore performed: the CSF analysis revealed a remarkable decrease of pleocytosis with a qualitative modification (only lymphocytes), and oligoclonal IgG bands were present. A new brain MRI was performed, showing a bilateral gadolinium-enhancement of the intrameatal VII and VIII cranial nerves bilaterally. In the hypothesis of a parainfective etiology, the patient was treated with oral steroid (Prednisolone 1 mg/Kg/daily), with a progressive and complete regression of the symptoms. We suggest that in this case, after a pathogen-drive immunological response (characterized by relevant CSF mixed pleocytosis and no evidence of IgGOB), a parainfective adaptive immunity-driven reaction (with mild lymphocyte pleocytosis and pattern III IgGOB after 9 days) against VII and VIII cranial nerves started. Indeed, steroid administration determined a rapid and complete restore of cranial nerve function.